Pengaruh Globalisasi Terhadap Perilaku Siswa Dalam Memahami Dan Menerapkan Nilai Pancasila Pada Kehidupan Sehari-Hari (Studi Kasus : Pada Siswa Kelas IX SMP Negeri 27 Medan) - Situmorang, Frandika; Siahaan, Parlaungan Gabriel; Purba, Novridah Reanti; Octaviani, Windi; Angkat, Febryanti; Nababan, Feryanto; Manurung, Christina (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research was studied to evaluate the influence of globalization which has an impact on student behavior in their understanding and application of Pancasila values in their daily lives. Through an empirical study involving 26 students from various backgrounds with a case study location at SMP Negeri 27 Medan, this research seeks significant empirical evidence about how globalization factors such as social media, culture and information technology influence how to understand and apply values. Pancasila values in everyday context. A descriptive approach is used for qualitative analysis in this research, the source of research data can be a questionnaire, namely a questionnaire where information can be obtained from direct research in the field. The findings of this research have a significant and relevant impact and it is hoped that these results will have an impact on in-depth insight into the role of globalization in helping to formulate more effective educational strategies for students' understanding of Pancasila values